Role for DUSP1 (dual-specificity protein phosphatase 1) in the regulation of autophagy. Issue 10 (2nd October 2016) - Wang, Juan; Zhou, Jun-Ying; Kho, Dhonghyo; Reiners, John J.; Wu, Gen Sheng
ABSTRACT: Accumulating evidence suggests that mitogen-activated protein kinases (MAPKs) regulate macroautophagy/autophagy. However, the involvement of dual-specificity protein phosphatases (DUSPs), endogenous inhibitors for MAPKs, in autophagy remains to be determined. Here we report that DUSP1/MKP-1, the founding member of the DUSP family, plays a critical role in regulating autophagy. Specifically, we demonstrate that DUSP1 knockdown by shRNA in human ovarian cancer CAOV3 cells and knockout in murine embryonic fibroblasts, increases both basal and rapamycin-increased autophagic flux. Overexpression of DUSP1 had the opposite effect. Importantly, knockout of Dusp1 promoted phosphorylation of ULK1 at Ser555, and BECN1/Beclin 1 at Ser15, and the association of PIK3C3/VPS34, ATG14, BECN1 and MAPK, leading to the activation of the autophagosome-initiating class III phosphatidylinositol 3-kinase (PtdIns3K) complex. Furthermore, knockdown and pharmacological inhibitor studies indicated that DUSP1-mediated suppression of autophagy reflected inactivation of the MAPK1-MAPK3 members of the MAPK family. Knockdown of DUSP1 sensitized CAOV3 cells to rapamycin-induced antigrowth activity. Moreover, CAOV3-CR cells, a line that had acquired cisplatin resistance, exhibited an elevated DUSP1 level and were refractory to rapamycin-induced autophagy and cytostatic effects. Knockdown of DUSP1 in CAOV3-CR cells restored sensitivity to rapamycin. Collectively, this work identifies a previously unrecognized role for DUSP1 in regulating autophagy and suggests that suppression of DUSP1 may enhance the therapeutic activity of rapamycin.